Vector-Valued Inequality of Fractional Integral Operator with Rough Kernel on Morrey-Adams Spaces - Daniel Salim; Yudi Soeharyadi; Wono Setya Budhi (IndoMS, 2022)
In 2019, Salim et al proved the vector-valued inequality for maximal operator with rough kernel on Lebesgue spaces and Morrey spaces. This results extend Fefferman-Stein inequality (1971). In 1970’s, Adams introduced another variant of Morrey spaces, which called as Morrey-Adams spaces. In this article, we prove vector-valued inequality for maximal operator and fractional integral operator with rough kernel on Morrey–Adams spaces.